Pengaruh Penambahan Probiotik Terhadap Indeks Putih Telur dan Indeks Kuning Telur Pada Ayam Niaga Petelur Afkir - Dwi Prahardhini; Rosidi Rosidi; Ibnu Hari Sulistyawan (Fakultas Peternakan Universitas Jenderal Soedirman, 2020)
Background. The purpose of this study was to observe the effect of probiotic addition on egg white index and egg yolk index of spent laying hens. Materials and methods. The material used in this research was Lohmann MB 402P spent laying hens age ± 88 weeks as many as 72 chickens. The feed used is basal feed and commercial probiotics containing Lactobacillus, Lactococcus, Streptococcus and Bifidobacterium. Basal feed used is complete feed with a protein content of 17,5 -18%. The equipment used is a battery cage size of 18 x 40 cm2 made of bamboo as much as 72 units, egg tray, thermo hygro, sliding pan, flat glass, haugh unit set, digital scales capacity 10 kg accuracy 0,01 and scales capacity 15 kg accuracy 0,03, spray equipment, measuring cups 50 and 10 ml, containers for mixing feed and cleaning tools. The maintenance period is 49 days with an adjustment period or 14 days prelim. Data collection was performed weekly for 5 times using 36 eggs from a total of 3 treatments so as to involve 180 eggs. The research method used was experiment with completely randomized design (CRD), using 3 treatments and each treatment was repeated 6 times. Each treatment unit was filled with 4 spent laying hens. P0 is basal feed plus probiotic 0 ml / kg of feed, P1 is basal feed plus probiotic 1 ml / kg of feed, P2 is basal feed plus probiotic 2 ml / kg of feed. Results. The results showed that the addition of probiotics had no significant effect (P> 0,05) on the white index and the yolk index. The average egg white index value is P0 0.033 ± 0.005; P1 0.028 ± 0.002; P2 0.032 ± 0.004. The average yolk index value was P0 0,451 ± 0,017; P1 0,460 ± 0.025; P2 0,456 ± 0.013. The conclusion of this study was that the addition of probiotics up to 2 ml/kg of feed has not been able to increase the index of white and egg yolks.